2018
DOI: 10.1016/j.pcad.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Precise Therapy for Thoracic Aortic Aneurysm in Marfan Syndrome: A Puzzle Nearing Its Solution

Abstract: Marfan Syndrome (MFS) is a rare connective tissue disorder, resulting from mutations in the fibrillin-1 gene, characterized by pathologic phenotypes in multiple organs, the most detrimental of which affects the thoracic aorta. Indeed, thoracic aortic aneurysms (TAA), leading to acute dissection and rupture, are today the major cause of morbidity and mortality in adult MFS patients. Therefore, there is a compelling need for novel therapeutic strategies to delay TAA progression and counteract aortic dissection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…Several studies have already shown that the type of underlying FBN1 gene variant has an influence on aortic outcome [ 62 , 63 , 64 , 65 , 66 ]. Patients harbouring variants predicted to result in haploinsufficiency (HI) of fibrillin-1 show a worse outcome than carriers of variants predicted to result in a dominant negative (DN) effect [ 67 ]. In the same vein, a genotype-phenotype relationship in the myocardium can be suspected.…”
Section: Pathophysiology Of Marfan Cardiomyopathymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have already shown that the type of underlying FBN1 gene variant has an influence on aortic outcome [ 62 , 63 , 64 , 65 , 66 ]. Patients harbouring variants predicted to result in haploinsufficiency (HI) of fibrillin-1 show a worse outcome than carriers of variants predicted to result in a dominant negative (DN) effect [ 67 ]. In the same vein, a genotype-phenotype relationship in the myocardium can be suspected.…”
Section: Pathophysiology Of Marfan Cardiomyopathymentioning
confidence: 99%
“…Similarly, in a smaller study by Rahman et al using three-dimensional speckle tracking echocardiography, LV EF, global LV circumferential strain and global LV area strain were all significantly lower in patients with variants predicted to result in HI than in those variants predicted to result in DN effect ( p < 0.05) [ 33 ]. Different types of FBN1 gene variants may also have a different effect on aortic elasticity [ 67 ], thereby potentially further contributing to impairment of myocardial function, but this has not been studied yet. In the aforementioned studies by de Witte et al and Loeper et al, the relation between aortic elasticity and predicted HI or DN effect of FBN1 gene variants was not evaluated [ 29 , 39 ].…”
Section: Pathophysiology Of Marfan Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…However, more clinical trials are required to verify the ability of ARBs to interfere with the MFS pathology. Even though several novel therapeutic strategies are under investigation, the goal of precision medicine is laborious to achieve [19]. Surgical intervention remains as the gold standard treatment strategy for aneurysm in MFS.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, an effective pharmacological treatment for this life-threatening disease in MFS patients still remains unknown. Thus, the complete identification of the mechanisms contributing to MFS aneurysm formation and the subsequent identification of novel therapeutic targets are clinical imperatives for this patients' category [6].…”
Section: Introductionmentioning
confidence: 99%